Fostering child & adolescent mental health in the classroom - Waller, Raymond J. (Sage Publications, 2006)
This guide for educators provides them with an outline of the most common mental health issues and symptomatology that they are likely to encounter in their daily work. Experts contribute to cover the variety of issues raised including specific essays on self injury, depression and parent-teacher communication.